CPK1-HSP90 phosphorylation and effector XopC2-HSP90 interaction underpin the antagonism during cassava defense-pathogen infection - Wei, Yunxie (The New phytologist, 2024)
© 2024 The Authors New Phytologist © 2024 New Phytologist Foundation.